VEGF-C is required for intestinal lymphatic vessel maintenance and lipid absorption - Nurmi, Harri (EMBO Mol Med, 2015)
Vascular endothelial growth factor C (VEGF-C) binding to its tyrosine kinase receptor VEGFR-3 drives lymphatic vessel growth during development and in pathological processes. Although the VEGF-C/VEGFR-3 pathway provides a target for treatment of cancer and lymphedema, the physiological functions of VEGF-C in adult vasculature are unknown. We show here that VEGF-C is necessary for perinatal lymphangiogenesis, but required for adult lymphatic vessel maintenance only in the intestine. Following Vegfc gene deletion in adult mice, the intestinal lymphatic vessels, including the lacteal vessels, underwent gradual atrophy, which was aggravated when also Vegfd was deleted. VEGF-C was expressed by a subset of smooth muscle cells adjacent to the lacteals in the villus and in the intestinal wall. The Vegfc-deleted mice showed defective lipid absorption and increased fecal excretion of dietary cholesterol and fatty acids. When fed a high-fat diet, the Vegfc-deficient mice were resistant to obesity and had improved glucose metabolism. Our findings indicate that the lymphangiogenic growth factors provide trophic and dynamic regulation of the intestinal lymphatic vasculature, which could be especially important in the dietary regulation of adiposity and cholesterol metabolism.